A Fuzzy Approach for Speckle Noise Reduction in SAR Images - Santoso, Ardhi W.; Bayuaji, Luhur; Pebrianti, Dwi; Suryanti, Awang; Lim, Tien Sze; Habibah, Lateh; Jasni, Mohamad Zain (IASE, 2016)
The Synthetic Aperture Radar (SAR) image has a high resolution and not influenced by weather conditions either day or night. SAR image with its advantages, is becoming popular than the optical image in earth observation using the remote-sensing techniques. However, the speckle noise that occurs in the SAR image causes difficulties in image interpretation. T hus, speckle noise reduction need s as prepossessing procedure prior to the u se of the SAR images. The ideal speckle filter has the capability of reducing speckle noise without losing the information and preserving texture. Fuzzy ap proach has a good performance to reduce speckle noise in a medical image, wh ich is occurred on a SAR image. It propo sed a filter which is a combin ation of fuzzy with qualified existing filter tha t applied to SAR image, aimed at eliminating speckle noise while maintaining texture. The results showed tha t the proposed filter has better perf ormance than commonly used filte rs such as the Mean, Median, Kuan, Lee, and Frost filters. The experiments conducted in a homogeneous area; forests, pla ntations and oceans from ALOS-P ALSAR image in the area of Kuant an, Pahang, Malaysia.